Potential antioxidative and anti-hyperuricemic components in Rodgersia podophylla A. Gray revealed by bio-affinity ultrafiltration with SOD and XOD - Liang, Can; Xu, Yongbing; Fan, Minxia; Muema, Felix Wambua; Chen, Guilin; Guo, Mingquan; Hu, Guangwan (Frontiers in Pharmacology, 2023)
This is a provisional file, not the final typeset article molecular docking simulation, with binding energies (BEs) ranging from -6.85 to -4.67 kcal/mol, and the inhibition constants (Ki) from 9.51 to 379.44 μM, which were better than the positive controls. Particularly, catechin exhibited a robust binding affinity towards XOD, with a BE value of -8.54 kcal/mol and Ki value of 0.55 μM, which surpassed the positive controls. In conclusion, our study revealed that R. podophylla possessed remarkable antioxidant and anti-hyperuricemia activities and that the UF-LC-MS method is suitable for screening potential ligands for SOD and XOD from medicinal plants.